Promoting Women's Economic Participation in India - Ghani, Ejaz; Kerr, William; O'Connell, Stephen D. (World Bank, Washington, DC, 2014)
Despite rapid economic growth, gender disparities in women's economic participation have remained deep and persistent in India. What explains these gender disparities? Is it poor infrastructure, limited education, or the composition of the labor force and industries? Or is it deficiencies in social and business networks and a low share of incumbent female entrepreneurs? This note analyzes the spatial determinants of female entrepreneurship in India in the manufacturing and services sectors. It finds that good infrastructure and education predict higher female entry shares. Gender networks also influence women's economic participation, as strong agglomeration economies exist in both manufacturing and services. A higher female ownership among incumbent businesses within a district-industry predicts a greater share of subsequent female entrepreneurs. Moreover, higher female ownership of local businesses in related industries (similar labor needs, input-output markets) predicts greater relative female entry rates. Unlocking female empowerment and entrepreneurship is a direct path to shared prosperity and a more dynamic and sustainable growth.